2020
DOI: 10.26480/trab.01.2020.18.23
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nutrients in Wheat: A Review

Abstract: Wheat (Triticum aestivum L.) is an important cereal crop that provides ample nutritious calories for humans and animals. The nutrient plays a vital role in the production of wheat. In this review, previous works were evaluated to investigate the role of nutrients, nutrient deficiency and toxicity in wheat. Both macro and micronutrients are necessary for wheat plants. Every nutrient has its own character and is involved in different metabolic processes of plant life. Nutrient deficiency and toxicity conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…Although these indices are more often an indicator for the nitrogen content in the leaves or canopy structure, as described by Walsh and Shafian [67], they could be a good indicator of micronutrient content in the plant as well as in the grains. Pandey et al [30] confirmed that the sufficient intake of micronutrients at right time and dosage can significantly increase the yield parameters of the wheat in terms of the number of spikes, height grains per spike, height of crops, among others. In the case of the selected varieties, the micronutrient content in the grains was in line with the height of both wheat varieties and affected the development of spikes in the Kabot variety.…”
Section: Evaluation Of Growth Parameters Under Different Tillagementioning
confidence: 96%
See 2 more Smart Citations
“…Although these indices are more often an indicator for the nitrogen content in the leaves or canopy structure, as described by Walsh and Shafian [67], they could be a good indicator of micronutrient content in the plant as well as in the grains. Pandey et al [30] confirmed that the sufficient intake of micronutrients at right time and dosage can significantly increase the yield parameters of the wheat in terms of the number of spikes, height grains per spike, height of crops, among others. In the case of the selected varieties, the micronutrient content in the grains was in line with the height of both wheat varieties and affected the development of spikes in the Kabot variety.…”
Section: Evaluation Of Growth Parameters Under Different Tillagementioning
confidence: 96%
“…al. [30] that specifically focuses on the use of thermal images for the purposes of water stress detection in crops. However, the relatively high temperatures (see Figure 3) in the first campaign were affected by very sparse vegetation, such as when the bare soil was visible.…”
Section: Evaluation Of Growth Parameters Under Different Tillagementioning
confidence: 99%
See 1 more Smart Citation
“…An important factor for increasing the efficiency of zero-till technology is an optimization of plant nutrition [25][26][27][28][29]. The balanced fertilization implies that crops are adequately supplied with nutrients at every stage of growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Tomato maturity is related to quantifiable parameters, including firmness and color, which represent biochemical changes during ripening according toZhang and McCarthy (2012). Inadequate nutrient implementation leads to sluggish growth, thin roots, shorter maturity, delayed plant maturation(Pandey et al 2020). Premature harvesting results in poor quality and deterioration at a faster rate than harvested at the proper stage of maturity.…”
mentioning
confidence: 99%